EXPLORING STUDENTS` PERCEPTIONS OF WRITING IN ENGLISH AS A FOREIGN LANGUAGE - Wildan As`at Taufik Hasibuan (Universitas Negeri Islam Sumatera Utara, 2025)
This study examines students' perceptions of writing in English as a Foreign Language, especially in terms of confidence, motivation, organization, and feelings toward writing. The research used a quantitative survey design and involved 16 students from the English Department at UIN SU, who participated voluntarily. Data were collected through a Likert-scale questionnaire containing ten statements about students' attitudes and challenges in English writing. The responses were analyzed descriptively using frequency and percentage data. The findings show that most students have positive perceptions of English writing. All students reported that they feel confident when writing and believe that writing helps improve their English skills. They also feel satisfied after completing writing tasks and agree that writing is important for their education. However, some students still experience difficulties, such as organizing ideas into coherent paragraphs, feeling stressed when working on long writing tasks, and being afraid of making mistakes. This indicates that although students value writing, they still face several cognitive and emotional challenges. Overall, the study suggests that writing instruction should not only improve language skills but also provide more support in organizing ideas, reducing anxiety, and increasing students' confidence in writing. These findings contribute to a better understanding of students' perceptions and support the development of more learner-centered EFL writing instruction.